Pengelolaan Arsip Dokumen Digital Dalam Sistem Informasi Penelusuran Perkara (SIPP) Di Pengadilan Agama Sumber - Dwi Astuti; Asep Saepulloh; Jefik Zulfikar Hafizd (Hukum, 2025)
Digital case-file management is essential for efficient, transparent, and accountable judicial administration. This study analyzes the implementation and legal governance of digital case archives through the Case Tracking Information System (SIPP) at the Sumber Religious Court. It employs empirical legal research with statutory, conceptual, and institutional approaches. Primary data derive from institutional observation and an interview with an archival staff member, while secondary materials consist of legislation, archival regulations, Supreme Court guidelines, SIPP manuals, and scholarly literature on electronic records and judicial administration. The data are qualitatively analyzed through five dimensions: authenticity and integrity, accessibility and retrievability, security and confidentiality, institutional capacity, and continuity of records management. The findings show that SIPP improves the speed of retrieval, supports case monitoring, reduces dependence on physical storage, and strengthens public access to procedural information. Nevertheless, implementation still faces unstable internet connections, server limitations, inconsistent document formats, software errors, uneven staff competence, resistance to digital work patterns, and the absence of sufficiently detailed internal procedures. From a legal perspective, SIPP data must be managed as electronic archives under Law Number 43 of 2009, Government Regulation Number 28 of 2012, and National Archives Regulation Number 6 of 2021. Effective management requires clear standard operating procedures, role-based access, metadata consistency, backup and disaster recovery, periodic audit, staff training, and integration between electronic records and original case files.